Room-temperature CO2 gas sensing material based on optical excitation In2O3 / g-C3N4 heterojunction material and preparation method of room-temperature CO2 gas sensing material
By using In2O3/g-C3N4 heterojunction material at room temperature, a heterostructure is constructed to enhance the photogenerated electron separation efficiency, solving the problems of room temperature CO2 detection sensitivity and energy consumption, and achieving high sensitivity and low energy consumption CO2 detection effect.
Patent Information
- Application Number
- CN202411439344.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art is difficult to accurately detect CO2 gas at room temperature, and the sensor energy consumption is high, which affects environmental protection development.
In2O3/g-C3N4 heterojunction material was prepared by solvothermal method and in-situ growth method. By constructing heterostructures, the separation efficiency of photogenerated electrons is enhanced, the CO2 detection sensitivity is improved, and energy consumption is reduced.
It realizes high sensitivity CO2 detection at room temperature and low detection limit, significantly improves the performance of the sensor and reduces energy consumption, and is suitable for environmental monitoring and industrial applications.
Smart Images

Figure CN119290789A_ABST
Abstract
Description
1. Technical Field
[0001] The present invention relates to the field of environmental monitoring and sensing technology, in particular to a sensing material capable of detecting CO2 gas by utilizing light-excited In2O3 / g-C3N4 heterojunction material at room temperature and a preparation method thereof. 2. Background Technology
[0002] Currently, due to the large-scale use of petroleum fuels and industrial emissions, the concentration of CO2 in the atmosphere is showing an upward trend, causing the greenhouse effect. Accurate CO2 concentration detection is an important means to cope with global climate change. It can be used to monitor the emission and absorption of CO2, which is related to the ecological environment and human survival. Room temperature CO2 sensors do not need to rely on high temperature to work, which will help expand the application of semiconductor sensors in all walks of life. The relatively low energy consumption of such sensors can reduce carbon emissions, which is in line with the current global environmental protection development trend. Therefore, it is very important and necessary to develop sensing semiconductor materials that can accurately detect CO2 at room temperature.
[0003] In2O3 hollow tube semiconductor materials have the advantages of high electron mobility, high specific surface area, good chemical stability and optical properties, and adjustable electronic structure due to their unique physical and chemical properties. These advantages make one-dimensional In2O3 hollow tube semiconductor materials have great potential in various applications, including photocatalysis, gas sensing, solar cells, field effect transistors, etc. Electrons can only move in one direction in this one-dimensional structured material, and its charge transfer efficiency is very high, which greatly optimizes the performance of its electronic devices. Due to its unique hollow tube structure, one-dimensional In2O3 materials have a high surface-to-volume ratio, which makes their electron transport performance excellent. At the same time, its optical properties are excellent and can absorb and emit light in a wide band. Constructing a semiconductor heterojunction with a matching band structure can effectively improve the charge separation efficiency of In2O3 and improve the sensitivity of In2O3 gas sensors. Among many semiconductors, g-C3N4 has a band structure matching In2O3 and good visible light absorption ability. The In2O3 / g-C3N4 heterostructure is constructed to improve the separation efficiency of photogenerated electrons, increase the number of carriers participating in the gas-sensitive reaction on the material surface, and improve the CO2 gas sensing performance of the gas-sensitive material at room temperature.
[0004] Based on the above considerations, this work uses the solvothermal method and in-situ growth method to prepare the In2O3 / g-C3N4 heterojunction material with g-C3N4 nanosheets loaded on the outside of the In2O3 hollow tube for visible light-excited CO2 gas detection at room temperature. By characterizing the prepared materials accordingly, the In2O3 / g-C3N4 with the best CO2 sensing performance was selected. III. Summary of the invention
[0005] The present invention aims to provide a sensor for detecting CO2 gas at room temperature using a light-excited In2O3 / g-C3N4 heterojunction material and a preparation method thereof. The sensor utilizes the excellent electronic properties of the In2O3 semiconductor material and the good visible light absorption performance of g-C3N4, and enhances the separation efficiency of photogenerated electrons by constructing a heterostructure, thereby improving the detection sensitivity of CO2 and reducing the energy consumption of the sensor.
[0006] In order to achieve the technical purpose of the present invention, the technical solution adopted by the present invention is as follows:
[0007] 1. Preparation of In2O3 hollow tubes: First, the In-MIL-68 precursor was synthesized by a hydrothermal method, and then calcined in an air atmosphere to obtain an In2O3 hollow tubular structure.
[0008] 2. Preparation of g-C3N4 nanosheets: g-C3N4 nanosheets were prepared by simply heating urea, and pure g-C3N4 nanosheets were obtained by centrifugation and washing.
[0009] 3. Preparation of In2O3 / g-C3N4 heterojunction material: In2O3 / g-C3N4 heterojunction material was prepared by in-situ growth method and subsequent calcination treatment, wherein the photoresponse performance of the material was optimized by adjusting the addition ratio of g-C3N4.
[0010] 4. Characterization and analysis: SEM and TEM were used to observe the morphology and confirm the microstructure of the material. XRD and FT-IR were used to determine the crystal structure and chemical composition of the material. UV-Vis and PL tests were used to evaluate the optical properties and electron-hole separation efficiency of the material.
[0011] 5. Sensing performance test: Different concentrations of CO2 were detected at room temperature and under visible light irradiation. The results showed that the In2O3 / g-C3N4 heterojunction material has extremely high sensitivity to CO2 and a detection limit as low as ppm, which is significantly better than a single In2O3 material.
[0012] Preferably, in step 1, 468 mg of In(NO3)3·xH2O and 180 mg of H2BDC are weighed and added into 40 ml of DMF.
[0013] Preferably, in step 2, 10 g of urea is weighed and placed in a tubular furnace, the heating rate is set to 2° C. / min, and the mixture is heated to 550° C. and maintained for 4 h.
[0014] Preferably, in step 3, the molar ratios of In2O3:g-C3N4 are 1:3, 1:5, and 1:7, respectively.
[0015] Preferably, in step 3, the In-MIL-68 / g-C3N4 obtained above is placed in a tube furnace, the heating rate is set to 5°C / min, maintained at 120°C for 2h in an air atmosphere, and heated to 450°C at 5°C / min and calcined for 2h.
[0016] Preferably, in step 5, an electrochemical workstation It is used for testing to obtain a curve of current variation with time, and data conversion is performed to obtain information on resistance variation with time, thereby obtaining information on CO2 concentration variation.
[0017] Figure 1 This is the SEM image of In-MIL-68, where a hexagonal prism structure with a large aspect ratio and a smooth outer surface are observed. In2O3 with a hollow tube structure is obtained by calcining it. It also shows In2O3 / g-C3N4 with a hollow tube structure obtained by further calcining after adding g-C3N4 during the synthesis of MOF.
[0018] Figure 2 The microstructure of g-C3N4 nanosheets, In2O3 and In2O3 / g-C3N4 hollow tube heterojunction materials was characterized by TEM. In the TEM image of In2O3 / g-C3N4 hollow tube heterojunction materials, it was found that g-C3N4 nanosheets were successfully loaded on In2O3.
[0019] Figure 3 The XRD patterns of In2O3 / g-C3N4-3, In2O3 / g-C3N4-2, In2O3 / g-C3N4-1 and In2O3 were used to analyze the phase of the samples. As the proportion of g-C3N4 increased, the peak value of the (002) crystal plane diffraction peak of g-C3N4 gradually increased, proving the successful synthesis of In2O3 / g-C3N4 heterojunction materials.
[0020] Figure 4 The prepared In2O3 hollow tubes, g-C3N4 nanosheets and In2O3 / g-C3N4 hollow structure heterojunction materials were tested by FT-IR to obtain chemical bond information to determine the sample composition. The characteristic peaks of In2O3 and g-C3N4 coexist in the heterojunction materials, further confirming the successful synthesis of the heterojunction material In2O3 / g-C3N4.
[0021] Figure 5 X-ray electron spectroscopy (XPS) can be used to analyze the chemical composition of materials and the electronic properties of interfaces. Analysis of the XPS spectrum shows that there is a strong interface interaction between In2O3 and g-C3N4, forming a heterojunction, and the charge transfer separation inhibits the recombination of photogenerated electron-hole pairs, thereby improving the gas-sensing performance of In2O3.
[0022] Figure 6 The visible light absorption capacity of g-C3N4, In2O3 and In2O3 / g-C3N4-2 was evaluated by UV-visible diffuse reflectance spectroscopy. The absorption band edge of In2O3 is about 450nm. After loading g-C3N4, the absorption band edge of the In2O3 / g-C3N4-2 heterojunction material red-shifts, and has an enhanced visible light absorption range compared with pure g-C3N4 and In2O3, respectively. This change is due to the formation of the heterojunction. In order to further explain the type of heterojunction between In2O3 / g-C3N4, the band gap Eg of In2O3, g-C3N4 and In2O3 / g-C3N4 was calculated, proving that the formation of a heterojunction between In2O3 / g-C3N4 causes electron transfer between components, which improves the light absorption capacity of the semiconductor material.
[0023] Figure 7 It is the Mott-Schottky curve of In2O3 and g-C3N4. The flat band potential is obtained by testing the Mott-Schottky curves of the two. The cross-intercept of the tangent line can represent the flat band potential of the semiconductor. The flat band potentials of In2O3 and g-C3N4 relative to the Ag / AgCl electrode are -0.09eV and -0.6eV respectively.
[0024] Figure 8 The photoluminescence PL spectrum can analyze the separation efficiency of photogenerated electron-hole pairs. Loading g-C3N4 can effectively inhibit the recombination of photogenerated electron-hole pairs. And the g-C3N4 loading amount has a certain effect on the PL peak of the heterojunction material. Among them, the PL peak intensity of In2O3 / g-C3N4-2 is the lowest, proving that the heterojunction material with this ratio has the best separation efficiency of photogenerated electron-hole pairs.
[0025] Fig. 9 In order to evaluate the sensing performance of gas-sensitive materials for CO2 gas at room temperature, In2O3, g-C3N4, In2O3 / g-C3N4-1, 2, 3 were tested under visible light and dark conditions at room temperature, with a target gas concentration of 400ppm CO2. It can be clearly seen that the gas response of In2O3, g-C3N4, In2O3 / g-C3N4-1, 2, 3 under visible light conditions is increased compared to dark conditions, proving that light excitation can improve the sensitivity of gas-sensitive materials to gas. Among them, In2O3 / g-C3N4-2 has the highest sensitivity to gas under visible light irradiation.
[0026] Fig.10To further prove that the In2O3 / g-C3N4 heterojunction material is sensitive to CO2 in the air, air is used as the balance gas to configure the CO2 target gas with an increased concentration relative to air, and air is used to purge under the same conditions and test it at room temperature using visible light irradiation. When the CO2 concentration in the air changes, the sensitivity increases with the increase in CO2 concentration. And the heterojunction materials with different proportions show the same response state, which can prove that the heterojunction material mainly responds to CO2 in the air.
[0027] The excellent effects of the present invention are as follows: 1. The multi-level nanostructure of the two-dimensional nanosheets loaded on the one-dimensional tube of In2O3 / g-C3N4 in the present invention effectively increases the reaction sites on the surface of the gas-sensitive material. Visible light irradiation on the surface of the semiconductor material successfully realizes CO2 gas sensing at room temperature and improves the gas-sensitive performance of the material.
[0028] 2. In2O3 / g-C3N4 hollow tube heterojunction material has better sensing performance. The sensitivity is nearly doubled compared to In2O3. And the performance of the material in desorbing CO2 in the absence of light is improved compared to In2O3. And by adjusting the loading amount of g-C3N4, a heterojunction gas-sensitive material with optimized sensing performance is obtained. Analysis shows that this is due to the formation of the heterojunction, which reduces the band gap and improves the visible light absorption capacity of the semiconductor material, and effectively inhibits the recombination of photogenerated electron-hole pairs, resulting in abundant carriers on the surface of the material to combine with CO2.
[0029] 3. The In2O3 / g-C3N4 heterojunction material of the present invention exhibits high sensitivity, low detection limit and good stability in room temperature CO2 sensor applications. The material works by using a photoexcitation mechanism without the need for additional heating, significantly reducing energy consumption and reducing environmental impact. In addition, the sensor exhibits good reusability and storage stability, and is expected to be widely used in environmental monitoring, industrial production safety, and indoor air quality assessment. IV. Description of the drawings
[0030] Figure 1 The SEM image and element mapping of the heterojunction material;
[0031] Figure 2 TEM and HRTEM images of heterojunction materials;
[0032] Figure 3 is the XRD pattern of heterojunction material;
[0033] Figure 4 FT-IR image of heterojunction material;
[0034] Figure 5 This is the XPS spectrum of the heterojunction material;
[0035] Figure 6 UV-vis DRS and Tauc plot of heterojunction materials;
[0036] Figure 7 Mott-Schottky curve for heterojunction materials;
[0037] Figure 8 Photoluminescence spectra and chronophotocurrent graphs of heterojunction materials;
[0038] Fig. 9 The room temperature sensing response-recovery curves of the heterojunction material to 400 ppm CO2 under light and dark conditions;
[0039] Fig.10 Dynamic response-recovery curves and fitting curves of heterojunction materials under continuous detection under visible light irradiation at room temperature. V. Specific implementation methods
[0040] To make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be described in detail below. The following examples are convenient for better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified.
[0041] Example 1
[0042] A method for preparing a heterojunction sensing material for CO2 gas detection at room temperature, characterized by comprising the following steps:
[0043] (1) Preparation of In-MIL-68: Weigh 468 mg of In(NO3)3·xH2O and 180 mg of H2BDC respectively, add them into 40 ml of DMF and fully dissolve them, react in an autoclave at 120°C for 2 h, then centrifuge at 3500 r / min for 10 min, wash with anhydrous ethanol and ultrapure water alternately to filter out the white precipitate, and place it in a vacuum drying oven for 12 h to obtain a white powder sample, namely In-MIL-68.
[0044] (2) Preparation of In2O3 hollow tubes: The In-MIL-68 obtained above was placed in a tube furnace, heated to 120°C and maintained for 2 h, and then heated to 400°C and calcined for 2 h to obtain a white powder sample, which is the In2O3 hollow tube.
[0045] (3) Preparation of g-C3N4 nanosheets: 10 g of urea was weighed and placed in a tube furnace, heated to 550°C for 4 h to obtain light yellow g-C3N4. The g-C3N4 was stirred in ultrapure water for 4 h, ultrasonically dispersed for 1 h, and dried in a vacuum drying oven for 12 h to obtain light yellow g-C3N4 nanosheets.
[0046] (4) Preparation of In2O3 / g-C3N4 heterojunction material: Weigh 468 mg of In(NO3)3·xH2O and 180 mg of H2BDC and add them to 40 ml of DMF to fully dissolve. According to the molar ratio of In2O3:g-C3N4 of 1:5, weigh 45 mg of g-C3N4 and add them to the mixed solution for ultrasonication for 30 minutes. Transfer the suspension to an autoclave and react at 120°C for 2 hours. Centrifuge at 3500 r / min for 10 minutes, wash and filter the white precipitate with anhydrous ethanol and ultrapure water alternately, place it in a vacuum drying oven and dry it for 12 hours to obtain a light yellow powder sample, namely In-MIL-68 / g-C3N4. The In-MIL-68 / g-C3N4 obtained above was placed in a tubular furnace, maintained at 120°C for 2 hours, heated to 450°C and calcined for 2 hours to obtain a white powder sample, which is the In2O3 / g-C3N4 heterojunction material with a nanosheet structure loaded outside the hollow tube.
[0047] The preferred embodiment 1 of the present invention has the highest sensitivity to CO2 gas under visible light irradiation, and the recovery performance is improved under dark conditions, which proves that the heterojunction material with a suitable ratio can achieve the best response to CO2 gas.
[0048] Example 2
[0049] The other conditions are the same as those in Example 1, except that in step (4), the molar ratio of In2O3:g-C3N4 is 1:3.
[0050] Example 3
[0051] The other conditions are the same as those in Example 1, except that in step (4), the molar ratio of In2O3:g-C3N4 is 1:7.
Claims
1. A method for preparing an In2O3 / g-C3N4 heterojunction sensing material for detecting CO2 gas at room temperature. The In2O3 / g-C3N4 heterojunction material with g-C3N4 nanosheets loaded outside the In2O3 hollow tube was prepared by a solvothermal method and an in-situ growth method, and was used for detecting CO2 gas excited by visible light at room temperature. It is characterized in that: The heterojunction material can improve the efficiency of photogenerated electron separation, increase the number of carriers participating in the gas-sensitive reaction on the surface of the material, and improve the CO2 gas sensing performance of the gas-sensitive material at room temperature.
2. According to claim 1, In-MIL-68 is obtained by high temperature reaction. In(NO3)3·xH2O and H2BDC are added to DMF and fully dissolved, and the mixed solution is transferred to a 100 ml autoclave and reacted at 120°C for 2 hours, washed, filtered and placed in a vacuum drying oven for 12 hours to obtain a white powder sample In-MIL-68.
3. According to claim 1, wherein In2O3 is a hollow tubular structure obtained by calcining an In-MIL-68 precursor. The In-MIL-68 obtained above is placed in a tube furnace, heated to 120°C for 2 hours, and then heated to 400°C for calcination for 2 hours to obtain a white powder sample, which is an In2O3 hollow tube.
4. According to claim 1, g-C3N4 is a nanosheet prepared by pyrolysis of urea. Urea is placed in a tube furnace and heated to 550°C for 4 hours to obtain light yellow g-C3N4. After ultrasonic dispersion and centrifugal filtration, it is dried in a vacuum drying oven for 12 hours to obtain light yellow g-C3N4 nanosheets.
5. According to claim 1, the molar ratio of g-C3N4 to In2O3 is 1:3, 1:5, and 1:7, respectively. The suspension is reacted in an autoclave at 120°C for 2 hours, and then the precipitate is separated by centrifugation and placed in a vacuum drying oven for 12 hours to obtain a light yellow powder sample, namely In-MIL-68 / g-C3N4.
6. The In2O3 / g-C3N4 heterojunction material prepared according to the method of claim 1 realizes CO2 gas sensing at room temperature.